2015
DOI: 10.1097/icu.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

PresbyLASIK approach for the correction of presbyopia

Abstract: Additional trials and standards for reporting results for presbyopic approaches are necessary. Careful patient selection and counseling is imperative in all PresbyLASIK treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Clinical outcomes using different techniques of presbyopic LASIK were reported and summarized in several recent studies. 3,5,29,30 The current development throughout the corneal surgical compensation for presbyopia in hyperopic patients indicates a converging trend toward hybrid techniques. Strategies involve a combination of different optical principles, including monovision, multifocality, asphericity modification, and pinhole, to improve visual outcomes.…”
Section: Generalization and Perspectivementioning
confidence: 99%
“…Clinical outcomes using different techniques of presbyopic LASIK were reported and summarized in several recent studies. 3,5,29,30 The current development throughout the corneal surgical compensation for presbyopia in hyperopic patients indicates a converging trend toward hybrid techniques. Strategies involve a combination of different optical principles, including monovision, multifocality, asphericity modification, and pinhole, to improve visual outcomes.…”
Section: Generalization and Perspectivementioning
confidence: 99%
“…Different authors such as Mosquera and Alió, Pallikaris and Panagopoulou and Alió et al have concluded that rigorous objective studies with adequately long follow‐up periods are necessary to better qualify the different presbyLASIK techniques. Most studies have only followed up patients for one year or less . The longest follow‐up reported by Epstein et al was 2.5 years, in a study concerning a peripheral presbyLASIK technique.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of presbyLASIK are affected by the progressive decay in accommodation that occurs with ageing, and criticisms have been raised about this type of LASIK surgery, as limited evidence has been reported in this regard . The subtle changes induced in the anterior corneal surface by the so‐called presbyLASIK techniques may be prone to regress due to epithelial compensation .…”
mentioning
confidence: 99%
“…Laser-assisted corrections [2023], intrastromal rings [24], corneal inlays [25, 26] and lenticular approaches [2729] attempt to address the presbyopia-related productivity loss and variable optical outcomes and satisfaction rates have been reported. Despite the variance of the published data, it is widely accepted that lenticular approaches offer an almost permanent surgical outcome for presbyopia since they address the ongoing or upcoming cataract changes of the lens as well, which are common in middle-aged and elderly presbyopes.…”
Section: Discussionmentioning
confidence: 99%